TiO2 -Supported Nano IrO2 Composite-Incorporated Ni-P Coating for Sensing Ethanol. (2016) - Shibli, S.M.A.; Suma, N.D.
Abstract: An amperometric ethanol sensor was developed by incorporating TiO2- supported nano IrO2 into electroless Ni-P coating. The existence of nano IrO2 composite in the coating caused enhancement of active surface area for ethanol oxidation. Ethanol sensing was carried out in 0.2 M NaOH solution. Incorporation of TiO2 considerably improved the physical properties of supported pure Ni-P electrode. The developed coating showed a response time of 17 sec and a sensitivity of 0.126 μA/ppm cm 2 .